Serological biomarkers for monitoring response to treatment of pulmonary and extrapulmonary tuberculosis in children and adolescents. (July 2020) - dos Santos, Danielle C.M.; Lovero, Kathryn L.; Schmidt, Christiane M.; Barros, Ana Cláudia M.W.; Quintanilha, Ana Paula; Barbosa, Ana Paula; Pone, Marcos V.S.; Pone, Sheila M.; Araujo, Julienne Martins; de Paula Martins, Camila; Cosme, Estela Magalhães; Dourado de Oliveira, Thais Raquelly; et al.
Abstract: Key measures to halt the spread of tuberculosis (TB) include early diagnosis, effective treatment, and monitoring disease management. We sought to evaluate the use of serum immunoglobulin levels against antigens present in cell envelope of Mycobacterium tuberculosis to monitor TB treatment response in children and adolescents with pulmonary (PTB) or extrapulmonary TB (EPTB). Blood samples were collected prior to and one, two, and six months following treatment initiation. Serum immunoglobulin levels against cardiolipin, sulfatide, mycolic acid and Mce1A protein were measured by ELISA. Serum from 53 TB patients and 12 healthy participants were analyzed. After six months of successful treatment, there was a significant decrease (p < 0.0001) in IgM levels against cardiolipin, sulfatide, mycolic acid and Mce1A protein and IgG levels against Mce1A protein when compared to baseline immunoglobulin levels. There was no significant variation in antibody levels during follow-up between participants with PTB and EPTB, confirmed and unconfirmed TB diagnosis, and HIV infection status. Antibody levels in control participants without TB did not decrease during follow-up. These results suggest that immunoglobulin responses to mycobacterial cell wall products may be a useful tool to monitor treatment response in children and adolescents with PTB or EPTB.